Implementasi Sistem Informasi Manajemen (Sim) Berbasis Aplikasi SIAGADalam Meningkatkan Pelayanan Administrasi Pada Seksi Pendidikan Agama Islam (Pais) Kementerian Agaman Kabupaten Kediri - Sukmawati, Anis; Kustantya, Fildza Maulida; Khozim, Ali (Program Studi Manajemen Pendidikan Islam, 2023)
Management Information System (MIS) is a system created to provide relevant information for managers who want to make decisions. For example, there is an application called SIAGA (religious teacher information and administration system) which is one of the SIM components that is being used in the religious ministry of Kediri district. This research aims to understand how SIM-based applications have helped the Islamic Religious Education (PAIS) section at the Ministry of Religion of Kediri Regency improve its administrative services. The research approach used is qualitative. The methods used in this research include interviews, observation and documentation. The conclusions of this research clearly show that the SIAGA application has the potential to improve administrative services in the PAIS Section located in the Kediri Regency Ministry of Religion.